2022
DOI: 10.3389/fimmu.2022.815609
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically-Mediated Inflammation and Cross-Presentation of Mycobacterium bovis BCG Proteins Stimulates Strong CD4 and CD8 T-Cell Responses in Mice

Abstract: Conventional vaccines are very efficient in the prevention of bacterial infections caused by extracellular pathogens due to effective stimulation of pathogen-specific antibodies. In contrast, considering that intracellular surveillance by antibodies is not possible, they are typically less effective in preventing or treating infections caused by intracellular pathogens such as Mycobacterium tuberculosis. The objective of the current study was to use so-called photochemical internalization (PCI) to deliver a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
(122 reference statements)
1
3
0
Order By: Relevance
“…Taken overall, these findings were consistent with the major roles of IFN-γ and multifunctional T cells in the protective immune response as previously described ( Cooper et al, 1993 ; Aagaard et al, 2009 ; Abel et al, 2010 ; Scriba et al, 2010 ; Sweeney et al, 2011 ; Green et al, 2013 ; Hu et al, 2019 ; Waeckerle-Men et al, 2022 ). We conclude that the association of Rv2299c with Ag85A in the DNA fusion vaccine provided an attractive starting point for the development of a multi-antigen DNA vaccine to boost BCG immunity without impairing the use of the current antigen-specific TB diagnostic tests.…”
Section: Discussionsupporting
confidence: 92%
“…Taken overall, these findings were consistent with the major roles of IFN-γ and multifunctional T cells in the protective immune response as previously described ( Cooper et al, 1993 ; Aagaard et al, 2009 ; Abel et al, 2010 ; Scriba et al, 2010 ; Sweeney et al, 2011 ; Green et al, 2013 ; Hu et al, 2019 ; Waeckerle-Men et al, 2022 ). We conclude that the association of Rv2299c with Ag85A in the DNA fusion vaccine provided an attractive starting point for the development of a multi-antigen DNA vaccine to boost BCG immunity without impairing the use of the current antigen-specific TB diagnostic tests.…”
Section: Discussionsupporting
confidence: 92%
“…Although both CD4 + and CD8 + lymphocytes are important for immune responses against BCG and TB through various mechanisms, 14,15 our analysis has shown that low CD8 + count is a significant risk factor for BCG-VACs compared with other lymphocyte subsets. This is probably caused by population and geographic heterogeneity in T-cell response against BCG vaccine.…”
Section: Discussionmentioning
confidence: 72%
“…Pathogen-speci c T-cell immunity is a crucial mechanism for host control of Mycobacterium tuberculosis infection [11]. Research in both human and animal models has demonstrated that acquired immunity against M. tuberculosis necessitates the participation of various T cell subsets, particularly CD4 + T cells and CD8 + T cells [12,13]. However, a patient's immune status should not only be assessed by enumerating immune cells but also by evaluating activated T cells [14,15].…”
Section: Discussionmentioning
confidence: 99%